Hazards of Nature, Risks to Development : An IEG Evaluation of World Bank Assistance for Natural Disasters - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The World Bank's Independent Evaluation Group examined the World Bank's experience in disaster prevention and response over the past 20 years and found that the scale of Bank operations has grown over the period. The report found that the Bank has demonstrated considerable flexibility in its approach, but actions have tended to be more reactive than proactive, with disaster response taking more of the focus that preventative measures.